Incidence and risk factors of prolonged recovery during procedural sedation in pediatrics - Cui, Yu; Wu, Qunying; Tang, Min; Chen, Qin; Kang, Lu; Mu, Qixia; He, Yani (Frontiers in Medicine, 2024)
Background Sedation-related adverse events not only referred to a cause for morbidity and mortality but also included events that could disrupt routine procedures and thus lead to reduced procedural efficiency or quality. To date, no literature is available to predict the risk factors associated with prolonged recovery in pediatric patients during procedural sedation. Thus, we retrospectively analyzed the two-year sedation data to explore the above questions. Methods Pediatric patients who underwent procedural sedation between January 2022 and January 2024 were retrospectively analyzed. The patients were divided into two groups according to sedation duration < 120 min (Non-prolonged recovery group); or ≧ 120 min (Prolonged recovery group). The primary outcome was the incidence of prolonged recovery. Risk factors associated with prolonged recovery were assessed. Results A total of 30,003 patients were identified; 854 (2.8%) developed prolonged recovery during procedural sedation. By multivariate regression, a higher body weight (OR 1.03, 95%CI 1.01-1.05), outpatients (OR 1.31, 95%CI 1.07-1.59), patients with sedation history (OR 1.25, 95%CI 1.07-1.44), and patients received chloral hydrate (OR 1.47, 95%CI 1.06-2.03), were associated with increased odds of the prolonged recovery with the initial sedative(s). Conclusions Monitoring time needs to be extended in patients with sedation history, those with heavier weights, outpatients, and those who received chloral hydrate.